Implementasi Manajemen Risiko Sistem Kesehatan, Keselamatan Kerja dan Lingkungan (K3L) pada Pembangunan Flyover Pegangsaan 2 Kelapa Gading Jakarta Utara - Hakim, Arif Rahman (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
On construction of Flyover Pegangsaan 2 Kelapa Gading Jakarta Utara until March 2016 there are 4 accidents. Therefore, the health, safety and environment management system’s applied to the implementation of construction works, thus minimizing the occurrence of occupational accidents and identify the risks from the highest to the lowest. Research methode is explaining variable and processing data at risk identification stage and risk analysis. The results obtained from the results of questionnaire given to 10 certified respondents and enrolled in A2K4 Indonesia and have experience at least 5 years in construction flyover. Assessment method using risk matrix sourced from AS/NZS 4360: 2004. The result of questionnaires is processed with risk index, the result’s that workers fall from height in reinforcment, formwork and parapet work get the biggest result with scale 13,8 and at The lowest rank is risk workers exposed to respiratory disorders due to the compressor on roadsign works with scale 5.5. In the risk matrix analysis there are 3 jobs that are categorized as high risk include worker falls from height at reinforcement, formwork and parapet, full electric shock on electrical installation work, and materials falls from a height and hit the worker in erection work.